Optimizing Bullying Prevention Policies and Programs through Civic Education in Junior High Schools in South Tangerang City - Susi; Rahayu, Yayuk Muji (Academy of Education Journal, 2025)
This study examines the optimization of policies and bullying prevention programs in two junior high schools in South Tangerang City through a civic education approach. This research employs a qualitative case study method. Data were collected through in-depth interviews, focus group discussions (FGD), and document analysis of school policies. Interviews were conducted with Guidance and Counseling (BK) teachers at SMPN 18 Tangsel and SMP Islam At-Taqwa Pamulang. NVivo 12 software was used to analyze bullying patterns and evaluate the effectiveness of prevention policies. The findings reveal that bullying predominantly occurs in verbal and social forms, mainly targeting groups perceived as different in academic, economic, or social aspects. Case identification is conducted through student reports, direct observation, and group discussions, while intervention involves individual counseling and discussions with homeroom teachers and parents. School policies, such as disciplinary regulations, the Special Handling Team (TTPK), and routine socialization programs, serve as the foundation for bullying prevention strategies. Although there has been a decrease in bullying incidents, challenges persist, particularly in the low reporting rate among students. Thus, this study recommends enhanced teacher training, the integration of civic education into the curriculum, and improved communication among school stakeholders to create a safer, more inclusive, and supportive school environment.